Produtividade e valor nutricional de cultivares de milheto sob adubação fosfatada - Firmino, Anderson Eugênio (2020)
Forage grasses are the main source of food for cattle, as it is the most economically viable source of dry matter. With the introduction of new species / cultivars of forage plants improved and adapted to the most different types of soils and edaphoclimatic conditions in Brazil, which allows a better performance of animals raised in exclusive grazing regime. In the region of Central Brazil, especially in the Cerrado, climatic conditions are defined by two seasons throughout the year: a rainy season, characterized by high forage production and, usually of good nutritional value, while the dry season that occurs between the months from April / May to October / November, with low forage production and low quality. It is believed that the seasonality of forage production is the biggest obstacle to the production of cattle under exclusive grazing regime, due to the great damage caused to the herd, whether in the production of meat or milk. In this way, there is a search for forages more adapted to the weather conditions that affect the forage production in the critical period of the year. In this context, forage millet appears as an alternative capable of contributing to the shortage of forage in the dry period of the year, in view of its physiological characteristics that allow it to adapt to acidic and low fertility soils, in addition to its high resistance to water stress. Two cultivars of forage millet were evaluated - ADR-500 and ADRf-6010, submitted to phosphate fertilization, in order to determine the potential of dry matter production and chemical composition in cut regime. The research was carried out at the Department of Zootechnics of the School of Veterinary and Zootechnics at UFG, from December 2018 to April 2019.